2011
DOI: 10.1007/s10725-011-9603-0
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone may interact with gibberellin to control apical dominance in pea (Pisum sativum)

Abstract: The role of strigolactones as plant growth regulators has been demonstrated through research on biosynthesis and signaling mutant plants and through the use of GR24, a synthetic analog of this class of molecules. Strigolactone mutants show a bushy phenotype and GR24 application inhibits the growth of axillary buds in these mutants, thus restoring the phenotype of a wild plant, which is characterized by a stronger apical dominance. In this work, we tested the effectiveness of this chemical on pea (Pisum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…S2 ). It is possible that in those species, gibberellin may play a role as a negative factor in controlling lateral bud outgrowth as reported in pea ( Scott et al 1967 , Luisi et al 2011 ), Arabidopsis ( Silverstone et al 1997 ) and Populus ( Mauriat et al 2011 , Zawaski and Busov 2014 ). Collectively, our results suggest that compared with the model plants Arabidopsis and pea, a more complex network regulates shoot branching in many perennial trees, in which gibberellin plays an important positive role.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…S2 ). It is possible that in those species, gibberellin may play a role as a negative factor in controlling lateral bud outgrowth as reported in pea ( Scott et al 1967 , Luisi et al 2011 ), Arabidopsis ( Silverstone et al 1997 ) and Populus ( Mauriat et al 2011 , Zawaski and Busov 2014 ). Collectively, our results suggest that compared with the model plants Arabidopsis and pea, a more complex network regulates shoot branching in many perennial trees, in which gibberellin plays an important positive role.…”
Section: Discussionmentioning
confidence: 92%
“…Although a negative correlation between gibberellin levels and branching or tillering has been observed in some species, such as Arabidopsis ( Silverstone et al 1997 ), pea ( Scott et al 1967 , Luisi et al 2011 ), rice ( Lo et al 2008 , Qi et al 2011 ), barley ( Jia et al 2009 , Jia et al 2011 ), turfgrass ( Agharkar et al 2007 ) and Populus trees ( Mauriat et al 2011 , Zawaski and Busov 2014 ), we found that gibberellin acts as a positive regulator in the regulation of shoot branching in the perennial woody plant J. curcas , demonstrated by direct GA 3 treatment ( Fig. 1 ) and by overexpressing the gibberellin biosynthesis gene JcGA20ox1 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are also two reports on a negative correlation between bioactive GA 1 levels and branching, as seen in Citrus and Chrysanthemum transgenic plants (Fagoaga et al, 2007;Miao et al, 2010). Interestingly, it has been proposed recently that GAs could change bud sensitivity to application of synthetic SLs (Luisi et al, 2011), as seen in dwarf pea plants with low GA 1 . Our results also suggest an interaction between SL levels and bud sensitivity to GA 3 .…”
Section: Sls Affect Ga 3 -Induced Sprout Releasementioning
confidence: 99%
“…Another group of hormones that are involved in the regulation of shoot architecture and act antagonistically toward SL are cytokinins that promote cell divisions and the outgrowth of axillary buds (Dun et al ). Moreover, not only a correlation between SL and GAs during the outgrowth of axillary buds in pea was reported (Luisi et al ), but also the independent action of SL and GA during the elongation of internodes was postulated (de Saint Germain et al ).…”
Section: Introductionmentioning
confidence: 99%